Feed preference of weaned pigs fed diets containing soybean meal, Brassica napus canola meal, or Brassica juncea canola meal - Landero, Jose L (J Anim Sci, 2018)
Brassica napus and Brassica juncea canola meal (CM) may replace soybean meal (SBM) in pig diets, but differ in fiber, glucosinolates content and profile. Preference of weaned pigs provided double-choice selections to diets containing 20% SBM, B. napus CM, or B. juncea CM was evaluated in two studies. In experiment 1, 216 pigs (9.4 ± 1.6 kg initial BW) were housed in 27 pens of 8 pigs (four gilts and four barrows). In experiment 2, 144 pigs (8.9 ± 1.1 kg) were housed in 36 pens of 4 pigs (two gilts and two barrows). Pigs were offered three dietary choices: B. napus CM with SBM as reference (B. napus CM [SBM]), B. juncea CM with SBM as reference (B. juncea CM [SBM]), and B. juncea CM with B. napus CM as reference (B. juncea CM [B. napus CM]) in a replicated 3 × 3 Latin square. Diets were formulated to provide 2.4 Mcal NE/kg and 4.5 g standardized ileal digestible Lys/Mcal NE and were balanced using canola oil and crystalline AA. Each pair of diets was offered in two self-feeders per pen as mash (experiment 1) or pellets (experiment 2) during three test-periods of 4-d, followed by a 3-d non-test period when a common diet was offered in both feeders. Feeders with different diets were rotated daily among pens during preference periods for both experiments, and feeder positions (right or left) were switched daily in experiment 2. Prior to the study and between periods, pigs were fed non-test diets containing SBM (experiment 1) or without test feedstuffs (experiment 2). Overall in both experiments, pigs preferred (P < 0.001) SBM over B. napus and B. juncea CM diets, and preferred (P < 0.001) B. napus over B. juncea CM diet. Dietary choice did not affect (P > 0.05) growth performance in both experiments, except for greater G:F (P < 0.05) for pigs fed the B. juncea CM [B. napus CM] diets than pigs fed the B. napus CM [SBM] or B. juncea CM [SBM] diets in experiment 1. In conclusion, weaned pigs preferred SBM over CM diets when given a choice, and preferred B. napus over the B. juncea diet that contained more total glucosinolates especially gluconapin. Weaned pigs fed the B. juncea CM [B. napus CM] diets in the double-choice selection did not reduce feed intake, weight gain, and G:F compared to pigs fed the B. napus CM [SBM] or B. juncea CM [SBM] diets.